2021
DOI: 10.24099/vet.arhiv.0867
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of thiol/disulfide homeostasis and ischemia-modified albumin levels to assess the oxidative stress in dogs with canine distemper

Abstract: This study aimed to investigate the diagnostic value of thiol/disulfide homeostasis (TDH) and ischemia-modified albumin (IMA) levels in evaluating oxidative stress in dogs with canine distemper. The study materials consisted of 24 cross-breed dogs: 18 dogs with canine distemper (CD group) and 6 healthy dogs as the control. Blood samples for analysis of antioxidant-oxidant parameters were taken from both groups. In addition to TDH parameters (native thiol [NT], total thiol [TT], and disulfide [Ds] levels and Ds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although many parameters, indicate oxidative stress in gastrointestinal system diseases, have been evaluated in the field of veterinary medicine in the current literature, there is no study investigating IMA levels. In a study on dogs with Canine Distemper (7), IMA, disulfide, % disulfide/native thiol ratio and % disulfide/total thiol ratio levels were higher, while native thiol, total thiol, % native thiol/total thiol ratio and albumin levels were significantly lower than the control group, and this was interpreted as canine distemper increased oxidative stress in dogs. The results obtained in our study are parallel to the studies conducted in the field of human and veterinary medicine, both in terms of TDH parameters and IMA levels.…”
Section: Discussionmentioning
confidence: 92%
“…Although many parameters, indicate oxidative stress in gastrointestinal system diseases, have been evaluated in the field of veterinary medicine in the current literature, there is no study investigating IMA levels. In a study on dogs with Canine Distemper (7), IMA, disulfide, % disulfide/native thiol ratio and % disulfide/total thiol ratio levels were higher, while native thiol, total thiol, % native thiol/total thiol ratio and albumin levels were significantly lower than the control group, and this was interpreted as canine distemper increased oxidative stress in dogs. The results obtained in our study are parallel to the studies conducted in the field of human and veterinary medicine, both in terms of TDH parameters and IMA levels.…”
Section: Discussionmentioning
confidence: 92%
“…(Yazıcı et al, 2002).Çetinkaya et al, (2020) reported that total thiol parameter was signi cantly lower in rat models of Alzheimer's disease compared to the control group. Similarly, Çamkerten et al,(2019) reported that total sulfhydryl group was importantly lower in pigs with sarcoptyx mange compared to healthy pigs Değirmençay et al, (2021). revealed that thiol levels were low in dogs with canine distemper.…”
mentioning
confidence: 92%
“…Değirmençay et al, 2021). Thiol groups, which try to prevent the damaging effect of free radicals, can not maintain plasma and tissue levels during these effects.…”
mentioning
confidence: 99%
“…The condition has been known to affect dogs and other carnivores and is one of the most infectious viral diseases with the highest fatality rate in dogs besides rabies [2]. Canine distemper virus (CDV) causes a multisystemic infection including the gastrointestinal, respiratory and nervous systems [3,4]. As a result of the viral spread to the central nervous system (CNS), multifocal demyelination occurs [3].…”
Section: Introductionmentioning
confidence: 99%